Diet and food insecurity among mothers, infants, and young children in Peru before and during COVID‐19: A panel survey - Rebecca Pradeilles; Rossina Pareja; Hilary M. Creed‐Kanashiro; Paula L. Griffiths; Michelle Holdsworth; Nervo Verdezoto; Sabrina Eymard‐Duvernay; Edwige Landais; Megan Stanley; Emily K. Rousham (Wiley, 2022)
Abstract The COVID‐19 pandemic may impact diet and nutrition through increased household food insecurity, lack of access to health services, and poorer quality diets. The primary aim of this study is to assess the impact of the pandemic on dietary outcomes of mothers and their infants and young children (IYC) in low‐income urban areas of Peru. We conducted a panel study, with one survey prepandemic (n = 244) and one survey 9 months after the onset of COVID‐19 (n = 254). We assessed breastfeeding and complementary feeding indicators and maternal dietary diversity in both surveys. During COVID‐19, we assessed household food insecurity experience and economic impacts of the pandemic on livelihoods; receipt of financial or food assistance, and uptake of health services. Almost all respondents (98.0%) reported adverse economic impacts due to the pandemic and 46.9% of households were at risk of moderate or severe household food insecurity. The proportion of households receiving government food assistance nearly doubled between the two surveys (36.5%-59.5%). Dietary indicators, however, did not worsen in mothers or IYC. Positive changes included an increase in exclusive breastfeeding <6 months (24.2%-39.0%, p < 0.008) and a decrease in sweet food consumption by IYC (33.1%-18.1%, p = 0.001) and mothers (34.0%-14.6%, p < 0.001). The prevalence of sugar‐sweetened beverage consumption remained high in both mothers (97%) and IYC (78%). In sum, we found dietary indicators had not significantly worsened 9 months into the COVID‐19 pandemic. However, several indicators remain suboptimal and should be targeted in future interventions.